Understanding "Understanding": Industrial Relations Research and Policy in Canada from 1969 to 1984...and Beyond - Arthurs, H.W. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
This paper is the H.D. Woods Memorial Lecture presented at the 1984 Annual Meeting of the Canadian Industrial Relations Association, Guelph, Ontario.